Sifat Fisis Komposit Pe/Nanosilika sebagai Fungsi Ketebalan - Tria Permata Sari; Posman Manurung; Agus Riyanto (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
Polyethylene (PE) has been widely used as the insulation material of high voltage cables because of its outstanding physical, chemical, and electrical properties. In this research the amorph nanosilica powders were extracted from pumice using NaOH, H2SO4 and HCl. PE and nanosilica was mixed by mixer at temperature 95 OC and then made the film by using barcoater. The weight percentage of nanosilica was 5 and 10% with thickness of 6, 12 and 25?m respectively. The PE/nanosilica were characterized via Fourier Transform InfraRed (FTIR) spectroscopy and LCR measurement to abtain conductivity and permitivity respons as a function of frequency. The effect thickness on the electrical properties of PE/nanosilica of 5 and 10 % for conductivity values in samples 25 ?m thick has a greater conductivity value. Whereas for the electrica constant of two filer variation shows that the thicker the sample, the greater the electric constant value. Where as for the dielectric constant of two filler variations shows that the ticker the sample, the greater the electric constant value.